Selective isotope labeling for NMR structure determination of proteins in complex with unlabeled ligands - Tripsianes, Konstantinos; Schütz, Ulrike; Emmanouilidis, Leonidas; Gemmecker, Gerd; Sattler, Michael (Journal of biomolecular NMR, 2019)
The physiological role of proteins is frequently linked to interactions with non-protein ligands or posttranslational modifications. Structural characterization of these complexes or modified proteins by NMR may be difficult as the ligands are usually not available in an isotope-labeled form and NMR spectra may suffer from signal overlap. Here, we present an optimized approach that uses specific NMR isotope-labeling schemes for overcoming both hurdles. This approach enabled the high-resolution structure determination of the farnesylated C-terminal domain of the peroxisomal protein PEX19. The approach combines specific 13C, 15N and 2H isotope labeling with tailored NMR experiments to (i) unambiguously identify the NMR frequencies and the stereochemistry of the unlabeled 15-carbon isoprenoid, (ii) resolve the NMR signals of protein methyl groups that contact the farnesyl moiety and (iii) enable the unambiguous assignment of a large number of protein-farnesyl NOEs. Protein deuteration was combined with selective isotope-labeling and protonation of amino acids and methyl groups to resolve ambiguities for key residues that contact the farnesyl group. Sidechain-labeling of leucines, isoleucines, methionines, and phenylalanines, reduced spectral overlap, facilitated assignments and yielded high quality NOE correlations to the unlabeled farnesyl. This approach was crucial to enable the first NMR structure of a farnesylated protein. The approach is readily applicable for NMR structural analysis of a wide range of protein-ligand complexes, where isotope-labeling of ligands is not well feasible.
Keywords: Protein Binding; konformace proteinů; Proteins; Molecular Structure; Ligands; Models, Molecular; Protein Conformation; Isotope Labeling; izotopové značení; ligandy; proteiny; molekulární modely; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární; molekulární struktura; vazba proteinů